If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -7c = 10c + -4 Reorder the terms: 30 + -7c = -4 + 10c Solving 30 + -7c = -4 + 10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. 30 + -7c + -10c = -4 + 10c + -10c Combine like terms: -7c + -10c = -17c 30 + -17c = -4 + 10c + -10c Combine like terms: 10c + -10c = 0 30 + -17c = -4 + 0 30 + -17c = -4 Add '-30' to each side of the equation. 30 + -30 + -17c = -4 + -30 Combine like terms: 30 + -30 = 0 0 + -17c = -4 + -30 -17c = -4 + -30 Combine like terms: -4 + -30 = -34 -17c = -34 Divide each side by '-17'. c = 2 Simplifying c = 2
| 5+3x=2+6x | | 3/4x+26=18 | | 4x-5x^2/x | | 2x-3(1)=-7 | | 26-3/4x=18 | | 5-3x=84+6x | | 12+14=3*f | | 5-3x=4+6x | | 6-8(5-3x)=0 | | 52+g=45+11 | | 2-6x=4+8x | | 4(6x-7)=32x | | 2-6x=14+8x | | z-51/6=116/7 | | 37+s=80/2 | | 3y-12x=18 | | H=16t^2-180t | | 2-3x=4+10x | | (3+2-2-1)(4+-1+-3)= | | 2-3x=4+8x | | 420/d=30 | | 2-3x=14+8x | | 5-3x=14+4x | | (5e^2j)/(4+5j) | | 5-3x=14+8x | | 57+4m=0 | | 5-3x=10+8x | | 5-6x=10+8x | | 5-6x=10+6x | | 2(-9.5)-3(1)= | | 100[0.07(x+7)]= | | 9(x+5)-9=40-3x-4+12x |